2022
DOI: 10.1128/jvi.00349-22
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal miR-138 Represses HSV-2 Lytic Infection by Regulating Viral and Host Genes with Mechanistic Differences from HSV-1

Abstract: HSV-1 and HSV-2 are closely related viruses with major differences. Both viruses establish latency in neurons from which they reactivate to cause disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The target sites are partially conserved among HSV-1, HSV-2, and chimpanzee herpesvirus 1. Repression of ICP0 by miR-138-5p is functionally conserved but mechanistically different between HSV-1 and HSV-2 [60]. Binding of miR-138-5p to both HSV-1 and HSV-2 ICP0 transcripts was confirmed by PAR-CLIP.…”
Section: Cellular Mirnas Directly Targeting Viral Lytic Transcriptsmentioning
confidence: 92%
See 1 more Smart Citation
“…The target sites are partially conserved among HSV-1, HSV-2, and chimpanzee herpesvirus 1. Repression of ICP0 by miR-138-5p is functionally conserved but mechanistically different between HSV-1 and HSV-2 [60]. Binding of miR-138-5p to both HSV-1 and HSV-2 ICP0 transcripts was confirmed by PAR-CLIP.…”
Section: Cellular Mirnas Directly Targeting Viral Lytic Transcriptsmentioning
confidence: 92%
“…OCT-1 is an HSV VP16 co-factor that mediates activation of viral IE gene transcription by binding to IE gene promoters [63]. FOXC1 is a newly identified host activator of replication of both HSV-1 and HSV-2 in neuronal cells [60,62]. FOXC1 broadly promotes HSV lytic gene expression by reducing heterochromatin on viral genes at early times of infection.…”
Section: Cellular Mirnas Repressing Cellular Pathways Important For V...mentioning
confidence: 99%
“…Host microRNAs also regulate lytic replication and latency in a similar manner, restricting viral IE gene expression (Figure 2A) [64]. The neuron-specific microRNA miR-138-5p represses the expression of ICP0 of both HSV-1 and HSV-2 [65,66]. miR-138-5p also restricts the expression of host transcription factors Oct-1 and FOXC1, both of which promote viral replication [67].…”
Section: Hsv-1 Lifecycle: Latent Infectionmentioning
confidence: 98%
“…In a recent study, it was reported that host miR-138 promotes HSV-1 latency by targeting the host OCT-1 and FOXC1 genes as well as the viral ICP0 gene [ 58 ]. However, during HSV-2 infection, the host miR-138 regulates the OCT-1, FOXC1, and viral ICP0 genes, as well as UL19 and UL20 genes, suggesting that alpha herpesviruses have evolved to exploit the neuronal miRNAs in order to promote viral latency [ 59 ]. Similarly, neurons expressing miR-138 target ICP0, the trans-activator of viral lytic gene.…”
Section: Mirna and Herpes Virusmentioning
confidence: 99%